Comparison of synbiotic beverages produced from riceberry malt extract using selected free and encapsulated probiotic lactic acid bacteria - Nakkarach, Atchareeya; Withayagiat, Ulaiwan (Agriculture and Natural Resources, 2018)
There has been much recent interest in probiotic products for lactose-intolerant consumers. This research developed a non-dairy synbiotic beverage from riceberry malt extract (RME). The objectives of the study were to select suitable lactic acid bacteria (LAB) and to compare the stabilities of products produced from free and encapsulated cells. Five LAB (Enterococcus faecalis N1-33, Lactobacillus acidophilus TISTR450, Lactobacillus johnsonii KUN119-2, Lactobacillus plantarum TC24 and Lactobacillus reuteri KUB-AC5) were tested for their ability to grow in RME, their survival under simulated gastrointestinal tract conditions and their antimicrobial activity. L. plantarum TC24 had the greatest probiotic potential. Comparisons of free versus encapsulated cell growth rates and their respective stabilities were carried out at two storage temperatures (8 °C and 30 °C) for 31 d. Calcium alginate encapsulation improved the survivability of L. plantarum TC24 under gastrointestinal tract conditions. However, the same treatment did not affect survivability under fermentation and storage conditions. Both free and encapsulated cell products could be stored at 8 °C for 15 d and the products retained viable cells at a level of 9 log colony forming units/mL. The encapsulated cell product was less preferable in consumer tests than the free cell product. The results suggested that RME has potential as a raw material for the production of nondairy synbiotic items for human consumption.